(untitled) (Journal of Medical & Health Sciences Review, 2025)
This increasing use of the copper oxide nanoparticles (CuO-NPs) in different industries has created great concern on the ecotoxicology effects of the nanoparticles on aquatic environments. This paper will include the assessment of the toxicological impact of the CuO-NPs on a freshwater fish model, which will combine a nanoparticle characterization analysis with a multi-level biological response. TEM, XRD, FTIR, DLS, and zeta potential were used to characterize synthesized CuO-NPs, which are characterized as crystalline monophasic, and positively charged on the surface, which promotes the colloidal stability and bio-interaction. Fish were subjected to various environmentally realistic levels and, it was found that copper accumulated in a dose-dependent way with the gills taking the lead followed by the liver and kidneys. This bioaccumulation elicited a cascade of the negative effects such as oxidative stress was observed by the initial increase and later inhibition of antioxidant enzymes (SOD, CAT, GPx) and a pronounced increase in lipid peroxidation (MDA). Moreover, exposure also resulted in severe genotoxicity, which was represented by the amplified formation of micronucleus and nuclear aberration as well as drastic histopathological harm at the tissues of the gill, liver and kidney. These sub-cellular injuries were observed as major behavioral changes whereby there was erratic swimming and poor feeding. The use of the integrated toxicity assessment proves that there is a definite correlation between physicochemical characteristics and multi-organ toxicity, and the ecological threat that CuO-NPs present to aquatic life is significant, which is why the development of strict guidelines in relation to this toxicogen is necessary.